Association of MMP9, HsCRP, and ESR with 5-ASA Treatment Duration and Disease Activity Based on Truelove and Witts Criteria in Patients with Diagnosed Ulcerative Colitis - Wardana, Vasa Adi Wisnu; Sugihartono, Titong; Miftahussurur, Muhammad (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Background: The American College of Gastroenterology (ACG) currently recommends the Truelove and Witts scoring system for evaluating Ulcerative Colitis (UC) disease activity. Inflammatory markers such as Matrix Metallopeptidase 9 (MMP-9), High-sensitivity C-Reactive Protein (HsCRP), and Erythrocyte Sedimentation Rate (ESR) have previously been shown to correlate with intestinal inflammation. To evaluate the association of MMP-9, HsCRP, and LED with disease activity and treatment duration in UC according to the Truelove and Witts criteria.Methods: An observational analytic study with a cross-sectional design was conducted involving subjects with UC diagnosed pathologically and receiving 5-ASA therapy at the Gastroenterohepatology Outpatient Department of Dr. Soetomo Hospital. MMP-9, HsCRP, and ESR serum levels were measured. The disease activity was determined based on the Truelove and Witts criteria. Analysis was done by spearman's correlation. P-values and correlation coefficients (r) were presented.Results: Among the 31 subjects, the majority were female (67.7%) with an average age of 46.84 years. Approximately 35.5% subjects had been treated for more than 6 months. The MMP-9 and HsCRP serum levels were above normal range (71% and 93.5% subjects, respectively). The majority (74.2%) of the subjects had normal ESR levels. Among the investigated inflammatory markers, only ESR levels significantly had a very weak positive correlation (p=0.010; r=0.004).Conclusion: ESR serves as an effective biomarker for UC disease activity compared to MMP-9 and HsCRP. Further study is warranted to explore the role of these biomarkers in UC management.